Congenital transmission of Neospora caninum in wild ungulates and foxes - Zanet, Stefania; Poncina, Manuela; Ferroglio, Ezio (Frontiers in Veterinary Science, 2023)
Introduction Neospora caninum is one of the main causes of abortion in cattle. In wildlife, the occurrence and relevance of vertical infection have not been yet clearly evaluated. The aim of this study was to verify the possibility of vertical transmission of N. caninum in three wild species extensively distributed in Europe, namely roe deer Capreolus capreolus, wild boar Sus scrofa and red fox Vulpes vulpes. Methods A total of 190 fetuses (72 wild boars, 67 foxes and 51 roe deer) from 61 females were included in the study. All animals, which were either found dead or culled within selective control plans in North-western Italy, were tested, in parallel by PCR on central nervous system, skeletal muscle and kidney. Results and discussion The efficiency of vertical transmission in the three target species was of 87.5% (95% CI 69.00–95.66).